Higher anti-tumor necrosis factor levels are associated with perianal fistula healing and fistula closure in Crohn's disease. Issue 1 (January 2020) - Plevris, Nikolas; Jenkinson, Philip W.; Arnott, Ian D.; Jones, Gareth R.; Lees, Charlie W.
Abstract : Objective: Limited data are available regarding the relationship between anti-tumor necrosis factor (TNF) drug/antibody levels and perianal fistula outcomes in Crohn's disease. The aims of this study were to assess the relationship between maintenance anti-TNF levels and perianal fistula outcomes. Methods: This was a retrospective cross-sectional study of patients receiving maintenance adalimumab or infliximab therapy (minimum 24 weeks) for the treatment of Crohn's disease with associated perianal fistulas, who had anti-TNF drug/antibody levels (trough for infliximab) measured within 4 weeks of clinical assessment. The primary outcome was the association of anti-TNF levels with perianal fistula healing defined as the absence of drainage. The secondary outcome was the association of anti-TNF levels with complete perianal fistula closure. Results: A total of 64 patients (adalimumab, n = 35; infliximab, n = 29) were included. Patients with fistula healing had higher levels of anti-TNF vs. those without fistula healing (adalimumab: 12.6 vs. 2.7 μg/mL, P < 0.01; infliximab: 8.1 vs. 3.2 μg/mL, P < 0.01). Patients with fistula closure also had significantly higher anti-TNF levels vs. those without fistula closure (adalimumab: 14.8 vs. 5.7 μg/mL, P < 0.01; infliximab: 8.2 vs. 3.2 μg/mL, P < 0.01). For adalimumab, receiver operator characteristic analysis identified an optimum level of >6.8 μg/mL and >9.8 μg/mL for fistula healing and closure, respectively. For infliximab, receiver operator characteristic analysis identified an optimum trough level of >7.1 μg/mL for both fistula healing and closure. Conclusion: Higher maintenance anti-TNF levels are associated with perianal fistula healing and closure in Crohn's disease. Abstract : Supplemental Digital Content is available in the text.